Mature Follicle Count and Multiple Gestation Risk Based on Patient Age in Intrauterine Insemination Cycles With Ovarian Stimulation - Evans, M. Blake (Obstet Gynecol, 2020)
OBJECTIVE: To estimate the risk of a multiple gestation pregnancy in ovarian stimulation intrauterine insemination (IUI) cycles when stratified by patient age and mature follicle number. METHODS: We conducted a retrospective cohort study at a single private practice fertility center of IUIs performed from 2004 to 2017. Intervention(s) were ovarian stimulation and IUI if post wash total motile sperm count was > 8 million. Mature follicles were defined as ≥ 14 mm as measured on the day of ovulation trigger. Main outcomes and measures were rates of clinical pregnancy and multiple gestation. RESULTS: We identified 24,649 women who underwent a total of 50,473 IUI cycles. Increasing the number of mature follicles from 1 to 5 at the time of IUI in women under 38 years of age increased the clinical pregnancy rate from 14.6% to 21.9% (aOR 1.6, 95%CI 1.4–1.9), almost entirely from a marked increase in multiple gestations per cycle from 0.6% to 6.5% (aOR 9.9, 95% CI 6.9–14.2). There was little increase in singleton pregnancies per IUI (14.1–16.4%) regardless of mature follicle number. The per pregnancy twin and higher order multiple gestation risk significantly increased (3.9% to 23.3%, P<0.01 and 0.2% to 10.6%, P<0.01, respectively) when comparing 1 versus 5 mature follicles present at the time of IUI (P<0.01). In women under 38 years with > 3 follicles present, over 1/4 of all pregnancies were multiples. Similar findings occurred in women 38 to 40 years. In women over 40, up to 4 follicles tripled the odds of pregnancy (aOR 3.1, 95%CI 2.1–4.5) while maintaining a less than 12% risk of multiple gestation per pregnancy, and a 1.0% absolute risk of multiples. CONCLUSION: Caution should be used in proceeding with IUI following ovarian stimulation when there are > 2 mature follicles in women under the age of 40 due to the substantially increased risk of multiple gestation without an improved chance of singleton clinical pregnancy.